Dynamic beamwidth control in partially reflective surface antennas : : doctoral thesis - Debogović, Tomislav (T. Debogović ; Fakultet elektrotehnike i računarstva, 2011)
In this work, a novel class of antennas, namely the partially reflective surface (PRS) antennas with dynamic beamwidth control, is investigated. It was found that the dynamic beamwidth control can be achieved by embedding varactor diodes or RF-MEMS switches in a PRS. These elements enable variation of the PRS reflection coefficient, which in turn causes directivity and beamwidth of the antenna to change. A mathematical model sufficient for a good definition of the antenna properties and requirements on the antenna design is developed. A number of specific types of reconfigurable PRS antennas are studied and validated using a full-wave simulator. For the purpose of the efficient full-wave analysis, a modelling procedure is developed. The procedure yields accurate results obtained in a short period of time. Using the modelling procedure, array-fed PRS antennas with scanning capability and bandwidth enlargement strategies are explored. Finally, theoretical key results are confirmed by measurements. -